Cold chain intervention and vacuum packaging to escalate the production of boneless milkfish in Pangkep - Rasdi, Rasdi; Alam, Syamsu; Muslimin, Istyqamah; Askar, Hardianty; Hijriani, Nurul (Universitas Muhammadiyah Magelang, 2025)
Limited cold chain facilities and conventional packaging systems are primary obstacles for fishery MSMEs in maintaining product quality. This community service program aims to enhance the production capacity and quality standardization of boneless milkfish at the Sipadecengi Business Group in Pangkep Regency. The implementation followed a participatory approach through the integration of freezer technology and vacuum sealers, complemented by hygiene processing training. Results showed significant escalation in key performance indicators: daily production capacity increased from 8–10 kg to 12–15 kg (50%), packaging efficiency rose by 33%, and product shelf life extended from 3 to 10 days under refrigeration. Beyond quantitative metrics, vacuum packaging significantly improved product aesthetics and protection against contamination. This initiative demonstrates that small-scale post-harvest technological modernization effectively strengthens the competitiveness and value-added of local fishery products.